Systemic sclerosis-like histopathological features in the myocardium of uPAR-deficient mice. Issue 2 (12th August 2015) - Manetti, Mirko; Rosa, Irene; Fazi, Marilena; Guiducci, Serena; Carmeliet, Peter; Ibba-Manneschi, Lidia; Matucci-Cerinic, Marco
Abstract : Objective: Cardiomyopathy is among the leading causes of death from systemic sclerosis (SSc). Urokinase-type plasminogen activator receptor (uPAR)-deficient mice have been recently reported to display important histopathological hallmarks of SSc, including dermal fibrosis, reduced dermal capillary density, and pulmonary fibrosis. Here, we investigated whether uPAR-deficient mice could display the histopathological features of SSc-related cardiomyopathy. Methods: Ventricular myocardial specimens from uPAR-deficient and wild-type mice at 12 and 24 weeks of age were analysed by both light microscopy and transmission electron microscopy. Picrosirius red staining and hydroxyproline content of myocardial specimens were quantified. Myofibroblast and microvessel counts were determined by immunofluorescence for α-smooth muscle actin and CD31, respectively. Endothelial cell apoptosis was assessed by a combined TUNEL/CD31 immunofluorescence assay. Expression of uPAR in human SSc and control ventricular myocardial autopsy specimens was determined by immunohistochemistry. Results: The myocardium of 24-week-old uPAR-deficient mice displayed focal ischaemic lesions with cardiomyocyte hypertrophy, myofibril rarefaction and contraction band necrosis. At 24 weeks of age, interstitial and perivascular collagen deposition and myofibroblast counts were significantly greater in myocardial tissue of uPAR-deficient mice than in wild-type mice. In uPAR-deficient mice, myocardial fibrosis was paralleled by microvascular endothelial cell apoptosis and reduced capillary density. uPAR expression was significantly downregulated in the myocardium of patients with SSc. Conclusions: Typical histopathological features of SSc-related cardiomyopathy are mimicked by uPAR-deficient mice. The downregulation of uPAR in the myocardium of patients with SSc may suggest similar underlying pathogenetic mechanisms. uPAR-deficient mice could be used as a preclinical model to study the mechanisms and therapeutic approaches of myocardial involvement in SSc.